Digital Marketing Analysis in the Hospitality Industry: Big Data Optimization - Vebry Haryati Lubis; Ofi Hidayat; Sony Tian Dhora; Asnawati; Rudy Effendi Listiyanto (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
This research analyzes digital marketing strategies in the tourism industry by optimizing Big Data. The methodology used is descriptive with a qualitative approach because the work is based on collecting existing information from other research work related to the problem of using digital marketing in the hospitality industry. Initially, the theoretical and conceptual basis of digital marketing, the tools it operates, and the concept of using Big data. Likewise, the changes generated by the hospitality industry, the new digital marketing strategies used by the hospitality industry with optimization of Big data, and how they affect their operations are analyzed. Finally, the benefits generated by the hospitality industry with the correct use of digital marketing strategies will be revealed, as it has been found that the results of using Big Data are profitable for business operations.